Shifting Power? Assessing the Impact of Transparency and Accountability Initiatives - and McGee, Rosie; Gaventa, John (IDS, 2011)
This paper arises from a review of the impact and effectiveness of transparency and accountability initiatives which gathered and analysed existing evidence, discussed how it could be improved, and ev...